A randomised controlled masked clinical trial of two treatments for osteoarthritis in dogs. Issue 7 (26th April 2021) - Whittem, T; Richards, L; Alexander, J; Beck, C; Knight, C; Milne, M; Rockman, M; Saunders, R; Tyrrell, D
Abstract : The product 4CYTE™ Canine (Interpath Pty Ltd., Ballarat, Victoria, Australia) contains four active ingredients: three marine‐derived ingredients and Epiitalis®, which is extracted from the seed of the plant Biota orientalis . Carprofen is a non‐steroidal anti‐inflammatory drug (NSAID) licensed for the treatment of osteoarthritis in dogs and is the active ingredient in several licensed products. This study aimed to compare the efficacy of 4CYTE Canine with carprofen for the treatment of pain from osteoarthritis. The trial was a randomised, masked, parallel group trial in dogs with naturally occurring osteoarthritis. Sixty‐nine dogs with body weight of between 10 and 50 kg were enrolled in the study, of which 66 (95.7%) completed the study. The 4CYTE Canine was administered at 60 mg active/kg daily and carprofen at 2–4 mg/kg daily, with a loading dose of up to 4 mg/kg on the first day. The trial duration was 28 days. The primary outcome was defined as improvement in Owner Lameness Score at Day 28 compared with Day 0. Other outcomes measured included Veterinary Lameness Scores and the Owner Mobility Scores. At Day 28, 14 of 29 (48.3%) dogs that received 4CYTE Canine and 13 of 37 (35.1%) dogs that received carprofen had improved. The 4CYTE Canine was found to be non‐inferior to carprofen at Day 14 for the Owner Mobility Score and at Day 28 for all three outcomes. This response pattern suggests that improvement in response to 4CYTE Canine continued between Days 14 and 28. These results support the conclusion that 4CYTE Canine is not inferior to carprofen by end‐point clinical efficacy.